-(m-6)=3m+4

Simple and best practice solution for -(m-6)=3m+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(m-6)=3m+4 equation:


Simplifying
-1(m + -6) = 3m + 4

Reorder the terms:
-1(-6 + m) = 3m + 4
(-6 * -1 + m * -1) = 3m + 4
(6 + -1m) = 3m + 4

Reorder the terms:
6 + -1m = 4 + 3m

Solving
6 + -1m = 4 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
6 + -1m + -3m = 4 + 3m + -3m

Combine like terms: -1m + -3m = -4m
6 + -4m = 4 + 3m + -3m

Combine like terms: 3m + -3m = 0
6 + -4m = 4 + 0
6 + -4m = 4

Add '-6' to each side of the equation.
6 + -6 + -4m = 4 + -6

Combine like terms: 6 + -6 = 0
0 + -4m = 4 + -6
-4m = 4 + -6

Combine like terms: 4 + -6 = -2
-4m = -2

Divide each side by '-4'.
m = 0.5

Simplifying
m = 0.5

See similar equations:

| x^2+4x-18=40 | | 6x+8-2=-24 | | 12/m-3 | | -5x+16+-8(x+1)=6x | | 2x^2-3y^2=12 | | 4m/m-3 | | -3+7=-5 | | -6x-x+10=15-7x | | 1-n-5+16=-n-2n | | (9v+36)(v^2-6v+5)=0 | | -(x+7)-6=-20+6x | | N^2+16=-8n | | 3[4x-5(y-2)]= | | -3x-1=x-17 | | -5=9+4 | | X+4(x+2)=12 | | -2(9+4s)=34 | | 5a^2= | | 3a+12=6a+7 | | 4x^3-6x-6=0 | | -7(1-5h)=21 | | 3x+2y+2x+5z+7y+2z= | | 5x+13y=11 | | 3x(4)=180 | | 4.5(6.2)=n | | 3(3y-3)-2(y-6)= | | m^2-3m+5=0 | | 35-6x=-(1-3x) | | 60+x+68+68=180 | | 48b+24= | | 4.5(6.2)= | | -76+x=-33 |

Equations solver categories